2019
DOI: 10.3390/f10010022
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Dynamics of Floodplain Forest Understory–Impacts of Degradation, Light Availability and Temperature on Biomass and Species Composition

Abstract: Forest understory significantly contributes to matter cycling in ecosystems, but little is known about its carbon pool. This is especially poorly understood in floodplain forests, one of the most threatened ecosystems worldwide. We studied seasonal dynamics of biomass and species composition of understory vegetation in degraded and non-degraded floodplain forests, to improve our understanding of carbon pools in forest ecosystems. We hypothesized that degraded and non-degraded floodplain forests will differ in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…The cover of plant species was assessed separately for each forest strata in April and July, and then pooled, to account for all species occurring in the understory by the year. These two dates are representative for floodplain forests, as Czapiewska et al [48] revealed that April and July are close to the centroid points representing seasonal shifts in understory vegetation seasonal composition; the above-mentioned study was conducted in our study area. During the study, we tallied only the understory layer, as shrubs and trees in parts of the forests were artificially planted and thus did not account for the spontaneous process of plant community assembly.…”
Section: Vegetation Characteristicsmentioning
confidence: 87%
“…The cover of plant species was assessed separately for each forest strata in April and July, and then pooled, to account for all species occurring in the understory by the year. These two dates are representative for floodplain forests, as Czapiewska et al [48] revealed that April and July are close to the centroid points representing seasonal shifts in understory vegetation seasonal composition; the above-mentioned study was conducted in our study area. During the study, we tallied only the understory layer, as shrubs and trees in parts of the forests were artificially planted and thus did not account for the spontaneous process of plant community assembly.…”
Section: Vegetation Characteristicsmentioning
confidence: 87%
“…For example, in eastern North American maple-beech forest the spring ephemeral Erythronium americanum occurs up to the beginning of June (Tremblay and Larocque 2001), similarly, in oak-beech-hornbeam forest in the Netherlands, the spring ephemeral Allium ursinum reaches peak biomass during a two-week period of May (Werger and Laar 1985). The biomass peak in the herb layer of non-degraded floodplain forest was observed at the end of May, and spring ephemerals were largely responsible for that (Czapiewska et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We sampled light availability in August, as our previous studies showed the lowest canopy openness and highest canopy foliage development during this month [24]. Although light availability varies across the growing season [26,28,32], its minimal value has the highest significance for understory vegetation and natural regeneration. Moreover, biomass models are based on samples harvested during full foliage development.…”
Section: Data Collectionmentioning
confidence: 99%
“…Our study explained that invasive tree species impact on light availability in forest ecosystems is mainly mediated by the increased quantity of foliage, not by more effective LAI to BA ratio.Light interception by canopy is one of the most important drivers of understory functioning. High light availability determines understory productivity [26][27][28]. It is also one of the most important drivers of plant species composition [24,29,30], as well as soil biota [21].…”
mentioning
confidence: 99%